2006
DOI: 10.1073/pnas.0607768103
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the corepressor of estrogen receptor activity (REA) enhances estrogen receptor function in the mammary gland

Abstract: Estrogen receptor (ER)-mediated gene expression plays an essential role in mammary gland morphogenesis, function, and carcinogenesis. The repressor of ER activity (REA) is an ER-interactive protein that counterbalances estrogen-induced ER transcriptional activity. Our previous study showed that genetic deletion of both REA alleles resulted in embryonic lethality. This study demonstrates that REA and ER␣ are coexpressed in mammary epithelial cells. REA heterozygous (REA ؉͞؊ ) mutant mice exhibit faster mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The relevance of the interaction between Skp2B and REA is strongly supported by the observations first that the transcriptional activity of the ER is increased in MCF-7-Skp2B cells and second that the expression of Skp2B in the mammary glands of transgenic mice mimics the phenotype observed for the REA heterozygous mice (15). As the 50% reduction in REA levels observed for Skp2B transgenic mice is equivalent to that observed for REA heterozygous mice and that this level of reduction was shown to be sufficient to induce the activity of the ER in vivo (15), the decrease of REA level observed for MMTV-Skp2B mice is likely to participate in the phenotype observed.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The relevance of the interaction between Skp2B and REA is strongly supported by the observations first that the transcriptional activity of the ER is increased in MCF-7-Skp2B cells and second that the expression of Skp2B in the mammary glands of transgenic mice mimics the phenotype observed for the REA heterozygous mice (15). As the 50% reduction in REA levels observed for Skp2B transgenic mice is equivalent to that observed for REA heterozygous mice and that this level of reduction was shown to be sufficient to induce the activity of the ER in vivo (15), the decrease of REA level observed for MMTV-Skp2B mice is likely to participate in the phenotype observed.…”
Section: Discussionmentioning
confidence: 49%
“…The best-characterized function of the ER is as a transcriptional factor, which is highly regulated by binding to coactivators and corepressors. Among the corepressors, the repressor of ER activity (REA) was recently shown to have a profound effect on the development of the mammary gland (14,15). REA heterozygote mice display accelerated invasion of the fat pad and development of the mammary gland during pregnancy, which is associated with an increase in the ER activity (15).…”
Section: Skp2bmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse primer specific to SV40 T mRNA was 5 ¶-ctgctcccattcatcagttcc-3 ¶. As an epithelial RNA loading control, the relative mRNA concentration of the keratin 18 epithelial marker was also analyzed by real-time RT-PCR as previously described (30).…”
Section: Methodsmentioning
confidence: 99%
“…However, since REA requires an intact F region, within the AF-2 domain (51) it is unlikely that altered expression would induce TAMr if AF-2 activity is compromised. Recent data from animal models have shown that REA is required for maintenance of ER activity and normal mammary gland development (52).…”
Section: Discussionmentioning
confidence: 99%